Reformed epistemology and naturalistic explanations of religious belief: an inquiry into the epistemological implications of the cognitive science of religion - Baker-Hytch, M (2014)
Reformed Epistemology is an influential view in contemporary philosophy of religion, according to which theistic beliefs that are the product of our native, non-inferential cognitive faculties often constitute knowledge if God exists. My aim in this thesis is to ascertain whether Reformed Epistemology is viable in light of contemporary scientific explanations of the mechanisms of religious belief- formation, especially the Cognitive Science of Religion (CSR). I argue for a qualified “yes.” To begin with, I attempt to carefully reconstruct and scrutinise some currently popular “debunking arguments” from CSR’s findings, which aim to show that non-inferential religious beliefs are not knowledge, even if true, given the causal origins that CSR ascribes to them. I try to show that in various ways these arguments fail. Subsequently, I attempt to find a better such argument. The strongest debunking argument, I contend, is one that focuses upon the diverse and mutually inconsistent outputs of the religious belief-producing mechanisms described by CSR. However, I go on to argue that even supposing that this argument succeeds in showing that religious beliefs that are partly the product of contingent cultural influences are not knowledge even if true, there remains a body of what I term “core propositions”—propositions concerning the existence of some kind of personal, supernatural creator and moral lawgiver, in which humans are naturally disposed to believe regardless of their particular cultural setting— that can be known if God exists. Finally, I try to show that merely having this core supernaturalistic knowledge would provide someone with the cognitive contact with God that is sufficient for having a personal relationship with God (if God exists), even if only de re relationship. I argue, moreover, that God would have positively good reasons for creating a world in which human beliefs about life’s most important matters, including religious matters, are significantly dependent upon testimony and hence subject to the ebbs and flows of cultural tides.